The Use Of Time-Loop Technique In Narrative - Muhammad Aminredza, Rosley (Universiti Malaysia Sarawak (UNIMAS), 2016)
Time-loop is an interesting technique that be used in a film to deliver a storyline in narrative. This research is about to make audiences easier to understand, follow and accept the time-loop technique in narrative. This research also shows how time-loop technique be used in films. Besides that, this research also show the function and effect of time-loop technique in narrative. This research get a concept of time-loop technique in a books, journals and website. This researchers also shown the time-loop technique that be used in certain films. Besides that, this research also get an opinion from a several film director and film critic in Malaysia. For solve the problem stated in this research, time-loop technique also can be used in a natural narrative to deliver a storyline because time-loop is only a technique. So, the time-loop technique is depends to a director or writer about how the director or writer want to use time-loop technique to deliver a storyline.